1998
DOI: 10.1039/a805941a
|View full text |Cite
|
Sign up to set email alerts
|

Diferrocenyl diselenides: excellent thiol peroxidase-like antioxidants

Abstract: Synthesis, structure and thiol peroxidase-like antioxidant activity of several diaryl diselenides having intramolecularly coordinating amino groups are described; the diselenides having both tertiary amino groups and redox-active ferrocenyl units show excellent peroxidase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 23 publications
0
74
0
2
Order By: Relevance
“…From the results obtained with this model, it can be stated that the enhancement of the catalytic reduction was linked to the presence of a selenium atom in the structure of the compound, but that the presence of selenium atom could not explain the variable effects of the tested compounds. According to the kinetic studies of Mugesh et al, 8 the diselenides with quite strong Se-N intramolecular interactions did not show noticeable activity, whereas the diselenides with an in-built co-ordinating basic amino group but no Se-N interaction showed excellent activity. These authors also reported that the diselenides, in which the selenium atom was directly bonded to a redox-active group such as ferrocenyl, showed a dramatic increase in peroxidase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results obtained with this model, it can be stated that the enhancement of the catalytic reduction was linked to the presence of a selenium atom in the structure of the compound, but that the presence of selenium atom could not explain the variable effects of the tested compounds. According to the kinetic studies of Mugesh et al, 8 the diselenides with quite strong Se-N intramolecular interactions did not show noticeable activity, whereas the diselenides with an in-built co-ordinating basic amino group but no Se-N interaction showed excellent activity. These authors also reported that the diselenides, in which the selenium atom was directly bonded to a redox-active group such as ferrocenyl, showed a dramatic increase in peroxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Various derivatives having in their structure either the diferrocenyl diselenide or ditelluride moieties were thus designed and synthesized. 8,9 In this series, diselenide derivatives bearing a primary amino group were not studied in the GPx mimic model.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has studied the thiol peroxidase-like activities of a series of intramolecularly coordinated diorganodiselenides where the donor atom is nitrogen [1][2][3][4]. The diselenide (1) without any Se···N intramolecular interaction exhibits better thiol peroxidase-like activity compared to the diselenide (2), which has a strong Se···N interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Organoselenenylsulfides have been proposed as intermediates in the catalytic cycle of glutathione peroxidase mimics [1][2][3][4][5][6][7]. Very few stable and structurally characterized selenenylsulfides are reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the design, synthesis, and evaluation of small-molecule selenium compounds that mimic the biological activity of GPx have been investigated by several groups, and selected examples 2 [28], 3 [29], 4 [30], and 5 [31] are presented in Scheme 2. Various diaryl diselenides [32][33][34][35][36][37][38] and certain types of tellurium compounds as well as dendrimeric and cyclodextrin-derived organochalcogen catalysts that emulate GPx have also been reported [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%